The Patterns of the Numbers used in Occupational Fraud Schemes - Paradita, Bella; Prasetyo , Eko; Astari, Ita Yoeli (Proceeding ICAMEKA: International Conference Accounting, Management & Economics Uniska, 2025)
Purpose - This study aims to determine the numbers used in financial statement fraud, corruption, and asset misappropriation schemes, thus enabling the design of an effective proactive analytics- based fraud detection test.Design/Methodology/Approach - The data sources used in this study were court records related to fraud prosecutions, investigative reports, and research papers related to fraud cases.Findings - Fraudulent numbers are most often round numbers, have strong period-to-period growth, fall just above or below internal control thresholds or other targets, are deviations from Benford's Law, are deliberate duplicates of authentic transactions, are outliers due to their excessive size, and are excessively rounded up or down. Limitations/Research Implications - The sample may not be representative of the population of detected and undetected frauds. Further research is needed to detect corruption/bribery schemes.Practical Implications - The results of this study are important for auditors and forensic accountants conducting proactive fraud detection tests. The discussion emphasizes that the analysis should include refinement and retesting, and then use clustering and filtering to address false positives. Originality/Value - This research provides an original, in-depth coverage of the patterns found in fraudulent numbers. The discussion section addresses implementation issues and considerations for future research